1991
DOI: 10.2135/cropsci1991.0011183x003100020012x
|View full text |Cite
|
Sign up to set email alerts
|

Basic Alfalfa Germplasms Differ in Nutritive Content of Forage

Abstract: Little information is available regarding comparative forage quality of alfalfa (Medicago sativa L.) leaves and stems of the nine germplasms from which most North American cultivars have been developed. In a greenhouse trial, forage quality of leaves and stems of the nine germplasms was compared when grown in a common environment and harvested at the same phenological stage. Germplasm sources (and representative cultivar) tested were: Indian (Sirsa #9), African (African), Peruvian (Hairy Peruvian), Flemish (Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 0 publications
3
22
0
Order By: Relevance
“…morphological model, flower colour and genotype. Such a variability of NDF confirms previous findings by Lenssen et al. (1991), Jung et al.…”
Section: Discussionsupporting
confidence: 92%
“…morphological model, flower colour and genotype. Such a variability of NDF confirms previous findings by Lenssen et al. (1991), Jung et al.…”
Section: Discussionsupporting
confidence: 92%
“…Other authors have found genetic variation for plant digestibility (Allinson et al, 1969) or stem digestibility (Heinrichs et al, 1969;Lenssen et al, 1991). Over the nine combinations of locations and cycles, the difference for plant digestibility was 2.5 points between Natsuwakaba and 63-28P.…”
Section: Methodsmentioning
confidence: 87%
“…These results were obtained with the calculation of stem digestibility through plant digestibility and leaf/stem ratio, assuming a constant leaf digestibility. A genetic difference for leaf digestibility has only been reported once (Lenssen et al, 1991), and this was probably due to the presence of one M falcata population. Significant correlation was observed between plant digestibility and stem height, induced by the correlations between leaf/stem ratio and plant height and between plant digestibility and leaf/stem ratio.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern alfalfa varieties have been used for genetic mapping (Segovia-Lerma et al, 2003; Ariss and Vandemark, 2007) and forage quality and water use efficiency (WUE; Lenssen et al, 1991; Ray et al, 1998, 2004; Segovia-Lerma et al, 2004). The method of carbon isotope discrimination was employed for measuring WUE.…”
Section: Introductionmentioning
confidence: 99%